A new fluorescence "turn on" nanoplatform based on conjugated polymer nanoparticles and Au nanorods for the detection of hyaluronidase. (January 2022) - Wang, Qiu-bo; Fu, Wen; Ma, Rui-jian; Lu, Qian; Liu, Zhao-e; Yao, Jin-shui; Liu, Qinze; Zhang, Xian; Zhao, Hui
Abstract: Hyaluronidase (HAase) is a momentous hydrolase related to many physiological and pathological processes. Therefore, it is urgent to establish a simple and accurate method for HAase detection. The combination of conjugated polymer nanoparticles (CPNs) and Au nanorods (AuNRs) provides an innovative method for platform design. In this work, a fluorescence platform was established for quantitative detection of HAase. Combined CPNs-NH2 and AuNRs using hyaluronic acid (HA) as the core by electrostatic adsorption, a novel "turn on" nanoplatform (CPNs-NH2 -HA@ AuNRs) was established. The fluorescence of CPNs-NH2 will be quenched because of the fluorescence resonance energy transfer (FRET) between CPNs-NH2 and AuNRs. In the presence of HAase, AuNRs can be effectively decomposed, leading to the recovery of CPNs-NH2 fluorescence. The lower limit of detection of CPNs-NH2 -HA@ AuNRs is obtained of 0.003 U/mL and the linear detection range is achieved within 1–45 U/mL. Furthermore, CPNs-NH2 -HA@ AuNRs was applied in practice to the determination of HAase with high selectivity and sensitivity. With its superior performance, it was successfully applied to HAase quantification in biological environment. The experimental results show that CPNs-NH2 -HA@ AuNRs is of great significance for the diagnosis of HAase related diseases. Graphical abstract: Image 1 Highlights: A novel sensor platform was constructed based on CPNs-NH2 and AuNRs using HA as the core. CPNs-NH2 -HA@ AuNRs nano-platform was highly sensitive to HAase with a lower detection limit of 0.003 U/mL. CPNs-NH2 -HA@ AuNRs nano-platform detected successfully HAase in actual samples.